2015
DOI: 10.1371/journal.pone.0139174
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Krill Oil Supplementation on Exercise Performance and Markers of Immune Function

Abstract: BackgroundKrill oil is a rich source of the long-chain n-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which may alter immune function after exercise. The aim of the study was to determine the effects of krill oil supplementation on post exercise immune function and performance.MethodsNineteen males and 18 females (age: 25.8 ± 5.3 years; mean ± S.D.) were randomly assigned to 2 g/day of krill oil (n = 18) or placebo (n = 19) supplementation for 6 weeks. A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Other measures that were found not to change with n-3 PUFA supplementation were neutrophil phagocytosis and oxidative burst, plasma IL-6 and cortisol, and PBMC IL-4 and IFN-γ production. Interestingly, we have also found similar results in our recent study employing krill oil (360 mg/day), versus placebo (oil mix similar to average European diet), when investigating young healthy individuals [54]. Summarising, it appears that n-3 PUFA does have some effect in modulating the immune system in the recovery period after exercise but whether it can reduce the incidence of URTI remains to be established.…”
Section: Immune Functionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other measures that were found not to change with n-3 PUFA supplementation were neutrophil phagocytosis and oxidative burst, plasma IL-6 and cortisol, and PBMC IL-4 and IFN-γ production. Interestingly, we have also found similar results in our recent study employing krill oil (360 mg/day), versus placebo (oil mix similar to average European diet), when investigating young healthy individuals [54]. Summarising, it appears that n-3 PUFA does have some effect in modulating the immune system in the recovery period after exercise but whether it can reduce the incidence of URTI remains to be established.…”
Section: Immune Functionsupporting
confidence: 83%
“…For instance, no differences in VO 2max , maximal power or endurance performance (time to completion) were found in healthy well-trained cyclists after 3 weeks of n-3 PUFA (6 g/day), n-3 PUFA + vitamin E (300 IU) or placebo (microcrystalline cellulose) [55]. These findings have been supported by recent work demonstrating no effect of n-3 PUFA supplementation on endurance performance or recovery in Australian Rules footballers (treadmill run to exhaustion) [48], well-trained cyclists (cycle to exhaustion) [46] or young healthy people (cycling simulated time trial) [54]. On the other hand, one study did find that n-3 PUFA supplementation (1.1 g/day), versus placebo (lactose monohydrate), resulted in a 3.7 mL kg − 1 min − 1 increase in VO 2max , alongside an increase in endothelial function, although no endurance performance measure was made [56].…”
Section: Endurance Performancementioning
confidence: 61%
See 1 more Smart Citation
“…Long-chain omega-3 polyunsaturated fatty acids (n-3 PUFA), in particular eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been shown to have a positive influence on the immune system in both humans and dogs (8,9). It occurs via various mechanisms (10), among others a shift from pro-inflammatory arachidonic acid (ARA)-derived mediators to less potent EPA/DHA-derived alternative inflammatory mediators (11,12).…”
Section: Abstract Introductionmentioning
confidence: 99%
“…Similarly, O'Keefe et al [32] found that patients with myocardial infarctions and depressed ejection fractions improved post-exercise HR recovery with 0.225 g/day of EPA and 0.585 g/day of DHA daily for 4 months. Conversely, EPA and DHA intake exhibited no changes in HR at rest or during a submaximal exercise [33][34][35]. Thus, although improvement of cardiac function can be assumed because of EPA and DHA intake, factors such as intake volume, period, and exercise load should be investigated in more detail in the future.…”
Section: Epa and Dha For Cardiovascular Functionmentioning
confidence: 99%